Biosynthesis of Pellucidin A in Peperomia pellucida (L.) HBK - de Moraes, Marcilio M.; Kato, Massuo J. (Frontiers in Plant Science, 2021)
Peperomia pellucida (L.) HBK (Piperaceae) (“jabuti herb”) is an herbaceous plant that is widespread in the tropics and has several ethnomedicinal uses. The phytochemical study of leaf extracts resulted in the isolation of 2,4,5-trimethoxycinnamic acid, 5,6,7-trimethoxyflavone, 2,4,5-trimethoxystyrene, 2,4,5-trimethoxybenzaldehyde, dillapiol and sesamin in addition to pellucidin A. The co-occurrence of styrene and cyclobutane dimers suggested the formation of pellucidin A by a photochemical [2+2] cycloaddition of two molecules of 2,4,5-trimethoxystyrene. To investigate this biogenesis, analysis of their contents throughout ontogeny and treatments such as drought, herbivory, jasmonic acid and UV360 light were carried out. Significant increases in the content of dillapiol (up to 86.0 %) were found when plants of P. pellucida were treated with jasmonic acid, whereas treatment under UV360 light increased the pellucidin A content (193.2 %). The biosynthetic hypothesis was examined by feeding various 13C-labeled precursors, followed by analysis with GC-MS, which showed incorporation of L-[2-13C]-phenylalanine (0.72%), [8-13C]-cinnamic acid (1.32%), [8-13C]-ferulic acid (0.51%), [8-13C]-2,4,5-trimethoxycinnamic acid (7.5%), and [8-13C]-2,4,5-trimethoxystyrene (12.8%) into pellucidin A. The enzymatic conversion assays indicated decarboxylation of 2,4,5-trimethoxycinnamic acid into 2,4,5-trimethoxystyrene, which was subsequently dimerized into pellucidin A under UV light. Taken together, the biosynthesis of pellucidin A in P. pellucida involves a sequence of reactions starting with L-phenylalanine, cinnamic acid, ferulic acid, 2,4,5-trimethoxycinnamic acid, which then decarboxylates to form 2,4,5-trimethoxystyrene and then is photochemically dimerized to produce pellucidin A.